Evaluative Stancetaking in English-Medium Academic Prose: A Study of Research Article Abstracts by Russian and Chinese L2 Writers - Olga Boginskaya (National Research University Higher School of Economics, 2024)
Background: Globalization has created the academic community's need to learn English in order to publish internationally and caused intensive research into academic prose by non-native writers with the aim of revealing prevailing culture-and discipline-specific rhetoric structures and suggesting ways of improving academic writing skills. Purpose: This contrastive study explored preferences in the employment of stance features in English-medium research article abstracts by second language writers from two different cultural backgrounds (Russia and China) assuming that variations in stancetaking are culturally shaped. Method: Hyland's (2005b) taxonomy of stance resources was adopted for the current study as the most comprehensive one including a wide range of writer-oriented features. This taxonomy can help identify pragmatic functions of linguistic markers used for stancetaking in academic prose. The methods of quantitative and qualitative analysis were applied. Results: A contrastive analysis of the findings showed that the Russian and Chinese academic communities manifest different stancetaking preferences. The quantitative analysis revealed that Chinese-authored RA abstracts contained considerably more stance features than those written by their Russian counterparts. Most quantitative differences between the application of stance features by Russian and Chinese authors were statistically significant. It was also revealed that while the Chinese academic writers seemed to be more careful in making claims, anticipating and acknowledging, the Russian scholars chose to create an impression of certainty and assurance, instilling confidence in their readers. The differences in the employment of stance features identified in the study are likely to reflect culture-specific writing peculiarities of the Chinese and Russian academic communities which favour slightly different discursive strategies. Conclusion: The findings carry pedagogical implications for academic writing course designers and can enhance L2 writers' familiarity with the culture-specific academic writing conventions in the knowledge domain.